Biological evaluation of synthetic α, β-unsaturated carbonyl based cyclohexanone derivatives as neuroprotective novel inhibitors of acetylcholinesterase, butyrylcholinesterase and amyloid-β aggregation. Issue 10 (15th May 2016) - Zha, Gao-Feng; Zhang, Cheng-Pan; Qin, Hua-Li; Jantan, Ibrahim; Sher, Muhammad; Amjad, Muhammad Wahab; Hussain, Muhammad Ajaz; Hussain, Zahid; Bukhari, Syed Nasir Abbas
Graphical abstract: The pharmacological evaluation of compounds comprises BuChE and AChE inhibition, amyloid β-induced cytotoxicity in PC12 cells and effects on self-induced Aβ aggregation. Abstract: A series of new α, β-unsaturated carbonyl-based cyclohexanone derivatives was synthesized by simple condensation method and all compounds were characterized by using various spectroscopic techniques. New compounds were evaluated for their effects on acetylcholinesterase (AChE) and butyrylcholinesterase (BuChE). These compounds were also screened for in vitro cytotoxicity and for inhibitory activity for self-induced Aβ1–42 aggregation. The effect of these compounds against amyloid β-induced cytotoxicity was also investigated. The findings of in vitro experiment revealed that most of these compounds exhibited potent inhibitory activity against AChE and self-induced Aβ1–42 aggregation. The compound3o exhibited best AChE (IC50 = 0.037 μM) inhibitory potential. Furthermore, compound3o disassembled the Aβ fibrils produced by self-induced Aβ aggregation by 76.6%. Compounds containing N -methyl-4-piperidone linker, showed high acetylcholinesterase and self-induced Aβ aggregation inhibitory activities as compared to reference drug donepezil. The pre-treatment of cells with synthetic compounds protected them against Aβ-induced cell death by up to 92%. Collectively, these findings suggest that some compounds from this series have potential to be promising multifunctional agents for AD treatment and our study suggest the cyclohexanone derivatives as promising new inhibitors for AChE and BuChE, potentially useful to treat neurodegenerative diseases.